Efektivitas E-Learning dalam Pembelajaran pada Pelajar Siswa SMA Negeri 13 Medan - Dedi Alfandi; A. Lailan Fadillah; E. Marnita Gulo; T. Rozan Fauzan; Siti Aisyah (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
This study aims to obtain information about the effectiveness of e-learning as a learning medium, especially for students of SMA Negeri 13 Medan. The methodology used is quantitative with interview data collection techniques and questionnaires conducted online. Based on the research findings, it shows that students respond well to the knowledge they know about e-learning. Although students respond well, there are obstacles that can hinder the effectiveness of e-learning as a learning medium, such as internet facilities for students who depend on internet and network packages to access e-learning itself. e-learning in learning becomes more effective.